Comparative Performance of Hybrid and Elite Inbred Rice Varieties with respect to Their Source-Sink Relationship. (29th January 2015) - Haque, Md Moinul; Pramanik, Habibur Rahman; Biswas, Jiban Krishna; Iftekharuddaula, K. M.; Hasanuzzaman, Mirza
Abstract : Hybrid rice varieties have higher yield potential over inbred varieties. This improvement is not always translated to the grain yield and its physiological causes are still unclear. In order to clarify it, two field experiments were conducted including two popular indica hybrids (BRRI hybrid dhan2 and Heera2) and one elite inbred (BRRI dhan45) rice varieties. Leaf area index, chlorophyll status, and photosynthetic rate of flag leaf, postheading crop growth rate, shoot reserve translocation, source-sink relation and yield, and its attributes of each variety were comprehensively analyzed. Both hybrid varieties outyielded the inbred. However, the hybrids and inbred varieties exhibited statistically identical yield in late planting. Both hybrids accumulated higher amount of biomass before heading and exhibited greater remobilization of assimilates to the grain in early plantings compared to the inbred variety. Filled grain (%) declined significantly at delayed planting in the hybrids compared to elite inbred due to increased temperature impaired-inefficient transport of assimilates. Flag leaf photosynthesis parameters were higher in the hybrid varieties than those of the inbred variety. Results suggest that greater remobilization of shoot reserves to the grain rendered higher yield of hybrid rice varieties.